Potential of bioremediation in treating aquaculture sludge: review article - Mohd Yaminudin, Nur Jasmin; Ismail, Muhammad Fadhil Syukri; Kamarudin, Mohd Salleh; Abd Karim, Murni Marlina (Elsevier, 2020)
Rapid development in shrimp farming has raised major concerns on the pond effluents that could negatively impacts the surrounding ecosystem triggered by the increased of the nutrients input. Sludge is formed due to large quantities of unwanted organic material mainly derived from excess feed and organic degradation. Due to its harmful effect, sludge need to be discharged from the culture ponds frequently. Appropriate treatment is needed before sludge could be discharged to the environment. One of the options that have gain interest of many researchers is through bioremediation process, which has been considered as an environmental friendly method in treating organic waste that does not involve any chemical usage. In this review, toxic components in aquaculture waste is discussed together with the potential of beneficial microbes in bioremediating aquaculture sludge.